Women’s satisfaction as an indicator of achieving a positive experience in midwifery continuity of care in Purwakarta Regency, West Java, Indonesia - Darmawan, Flora Honey; Fuad Wirakusumah, Firman; Ruluwedrata Rinawan, Fedri; Purbasari, Ayi; Waslia, Dede (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Midwives as providers of continuous midwifery care have a strategic position to play a role in efforts to overcome reducing MMR and IMR. An important aspect of continuous midwifery care is developing a quality relationship between midwives and women that will increase client satisfaction with the care provided. Continuity models of midwifery care have been proven beneficial to women and babies and are highly recommended by WHO as one important factor when it comes to creating a positive birth experience.Objective: The purpose of this study was to determine how women's satisfaction as an indicator of a positive experience in sustainable midwifery care in PurwakartaMethods: This research is a Quasi Experimental with Posttest-Only approach with Non-Equivalent Groups Design. The experimental group was pregnant women up to the postpartum period who received continuous midwifery care while the comparison group was women who did not receive continuous midwifery care. Data analysis in this study used the Wilcoxon Signed Rank test.Results: There was an association between client satisfaction and continuous midwifery care, both in pregnancy, labor and postpartum period (p value <0.05).Conclusion: Women who received continuous midwifery care had higher satisfaction and positive experiences.